PERBEDAAN KARIES GIGI YANG MENGKONSUMSI AIR PDAM DENGAN AIR SUMUR BOR DI DESA BINJAI PUNGGAL DENGAN DESA 7 DI KECAMATAN HALONG KABUPATEN BALANGAN - firdaus, ahmad; amperawati, metty; nuryati, sri (Poltekkes Kemenkes Banjarmasin, 2022)
The dental and oral health is part of body health which can affect overallbody health. Dental caries is a problem of dental and mouth infections that are stillcommon in Indonesia. One of the factors causing high oral and dental healthproblems is the low pH level in water.This study aims to determine the differences in dental caries between consumingPDAM water and wellbore water at Desa Punggal Village and Desa 7 in KecamatanHalong, Kabupaten Balangan. The descriptive quantitative methode was used withobservational analytic. The population was all of Desa Binjai Punggal and Desa 7 inKecamatan Halong Kabupaten Balangan. Samples were taken using purposivesampling technique with the criteria of citizens aged ranges> 17 years. The number of samples is 40 respondents. The technique of analyzingused the Independent Sample T-Test test data with a confidence level of 95%.Results showed that the dental caries that consumed PDAM water were low that is2 people (10%), moderate 13 people (65%) and high 5 people (25%). Meanwhile,dental caries that consumed drilled well water were 9 people (45%) in the mediumcategory and 11 people (55%) high. Independent Sample T-Test results show that thevalue of Sig. (2-tailed) p = 0.027 means that there are significant differencesconducted.The conclusion of this study that there are significant differences in dental cariesthat consume PDAM water with wellbore water both in Desa Binjai Punggal and Desa 7at Kecamatan Halong, Kabupaten Balangan. Socialization is needed to the communityand local government in providing drinking water to the population with efforts toimprove the community's oral health.